Super-resolution microscopy to study membrane nanodomains and transport mechanisms in the plasma membrane - Zulueta Diaz, Yenisleidy de las Mercedes; Arnspang, Eva C. (Frontiers in Molecular Biosciences, 2024)
Biological membranes are complex, heterogeneous, and dynamic systems that play roles in the compartmentalization and protection of cells from the environment. It is still a challenge to elucidate kinetics and real-time transport routes for molecules through biological membranes in live cells. Currently, by developing and employing super-resolution microscopy; increasing evidence indicates channels and transporter nano-organization and dynamics within membranes play an important role in these regulatory mechanisms. Here we review recent advances and discuss the major advantages and disadvantages of using super-resolution microscopy to investigate protein organization and transport within plasma membranes.